What Is the Role of Human Oversight in Medical AI? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
The integration of artificial intelligence (AI) into healthcare is rapidly transforming the medical landscape, from diagnostic imaging to personalized treatm...
Keywords: AI Ethics in Healthcare; Human; Oversight; Medical; Artificial Intelligence; Healthcare; Digital Health